Representasi Budaya dan Profil Pelajar Pancasila di Buku Pelajaran Bahasa Indonesia Kelas VII - Puspitasari, Alfi; Andayani, Andayani; Setyoningsih, Titi (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to (1) describe the representation of culture in Indonesian textbooks grade VII, (2) describe the representation of Pancasila student profile in Indonesian textbooks grade VII. This research is a qualitative research and uses case study method with content analysis approach. The data source of this research is the seventh grade Indonesian textbook. The sampling technique was done by purposive sampling. Data collection was done by document analysis. The data validity test technique used was data source triangulation. The results of this study are, in the seventh grade Indonesian textbooks, cultural representations are found to be described through Koentjaraningrat's cultural elements in the form of language, technological systems, livelihood systems, social organization, knowledge systems, religious systems, and arts. Second, in the seventh grade Indonesian textbook, there is a representation of the Pancasila student profile which is divided into six dimensions, namely faith, fear of God Almighty; and noble character; global diversity; mutual cooperation; independent; critical reasoning; and creative. In the discussion, the six dimensions are then further divided based on the existing key elements